Tata Kelola Pengelolaan Pariwisata Di Kawasan Ekonomi Khusus Tanjung Lesung - Soviah, Siti; Maulana, Delly; Nugroho, Arif (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
This Study aims to determine the tourism Management Governance in Special Economic Zone of Tanjung Lesung. This Research method is descriptive qualitative. Data accumulation techniques used are: Interview, Documentation, and observation. The location of this research is around the Tanjung Lesung KEK tourism area. Based on the results of this study it can be concluded: First. Tourism Management in Pandeglang Regency, especially in the Tanjung Lesung Special Economic Zone Tourism area run accordance with several indicators of tourism managementOf all indicators on the road well but for public relations the private sector and the government has done its best but it is deniable that conflicts often occur, but it can be resolved well, because nothing is difficult as long as there is good intention; and second. Public Private Partnership is agreement or contract between the private and the government based, based on that the transfer of function is left to the private sector from the regional Government and determined based on existing regulations.